El corazón de la mujer - Arocha R., J. Ildefonzo (Revista Hospital Clínico Universidad de Chile, 2019)
In the vast majority of cardiovascular diseases (CVDs), there are well-described differences between women and men in epidemiology, pathophysiology, clinical manifestations, effects of therapy, and outcomes. These differences arise on one hand from biological differences among women and men, which are called sex differences, due to differences in gene expression from the sex chromosomes and subsequent differences in sexual hormones leading to differences in gene expression and function in the CV system, In contrast, gender differences are unique to the human. They arise from sociocultural processes, such as different behaviours of women and men; exposure to specific influences of the environment; different forms of nutrition, lifestyle, or stress; or attitudes towards treatments and prevention. The scientific societies are at the forefront of implementing the knowledge in research and healthcare strategies with more proactive attitude for a feminine centered approaches may lead to a more specific and effective use of resources in CVD prevention and therapy in women.